The Pregnant Surgeon - Harnsberger, Cristina R.; Davids, Jennifer S. (Clinics in Colon and Rectal Surgery, 2019)
The proportion of women entering medicine and surgery is increasing steadily. As more women surgeons have children during residency and practice, it is essential that we adopt a team approach to the pregnant surgeon, as a pregnancy undoubtedly impacts the team and not just the individual. Coauthored by a practicing surgeon mother of 2 (J. D.) and a postgraduate year 8 colorectal surgery fellow mother of 2 who is currently pregnant (C. H.), we aim to review the data while providing some practical advice for pregnant surgeons and those considering pregnancy, as well as their valued colleagues, mentors, and administrators. Physical challenges are discussed by trimester, as are the risks facing the pregnant surgeon, the logistics of transitioning in and out of maternity leave, and postpartum considerations.
Keywords: pregnant surgeon; breastfeeding surgeon; maternity leave; parental leave